Los trabajos de la Comisión Topográfica en La Paz, Bolivia, a mediados del siglo XIX y la construcción del Estado nacional - Machaca, Victor Hugo (Pontificia Universidad Católica del Perú, 2023)
This article shows the work of the members of the Topographic Commission in La Paz, Bolivia, in order to understand the consolidation of the national State through cartography in the mid-nineteenth century. The city of La Paz was the center of its activities for the elaboration of an urban plan, a topographic map of the department and another of Lake Titicaca, which are analyzed in the context of the elaboration of a national geographical map. To develop this research, information from archives and libraries of different Bolivian cities and the National Historical Archive of Spain has been consulted.

En este artículo se muestran los trabajos de los miembros de la Comisión Topográﬁca en La Paz, Bolivia, con el ﬁn de entender la consolidación del Estado nacional a través de la cartografía a mediados del siglo XIX. La ciudad de La Paz fue el centro de sus actividades para el levantamiento de un plano urbano, un mapa topográfico del departamento y otro del lago Titicaca, los cuales son analizados en el contexto de elaboración de una carta geográfica nacional. Para desarrollar esta investigación se ha consultado información de archivos y bibliotecas de distintas ciudades bolivianas y del Archivo Histórico Nacional de España.
The work of the Topographic Commission in La Paz, Bolivia, in the mid-19th century and the construction of the national State
Keywords: La Paz; Topographic Commission; Maps; Urban plans; 19th century; La Paz; Comisión Topográfica; Mapas; Planos urbanos; Siglo XIX; https://purl.org/pe-repo/ocde/ford#6.00.00